Biocatalytic Reduction of HMF to 2, 5‐Bis(hydroxymethyl)furan by HMF‐Tolerant Whole Cells. Issue 2 (18th January 2017) - Li, Yan‐Mei; Zhang, Xue‐Ying; Li, Ning; Xu, Pei; Lou, Wen‐Yong; Zong, Min‐Hua
Abstract: Invited for this month′s cover is the group of Min‐Hua Zong at South China University of Technology. The image shows the selective synthesis of 2, 5‐bis(hydroxymethyl)furan from 5‐hydroxymethylfurfural (HMF) using highly HMF‐tolerant whole cells. The Full Paper itself is available at 10.1002/cssc.201601426 . Abstract : "we named this cover image "The Conductor and Its Players"…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201601426 . View the Front Cover here:10.1002/cssc.201700003 .